The Role of Patch Repair in Aortic Arch Reconstruction: Enhancing Outcomes and Preserving Growth Potential in Pediatric Patients - Serkan Seçici; Seyyit Bahaettin Öncü (Kardiyovasküler Tıp E Dergisi/E Journal of Cardiovascular Medicine)
Objectives: Aortic arch abnormalities are frequently observed in neonates and may be associated with other congenital cardiac anomalies. Various surgical approaches exist for the repair of these abnormalities. This study aimed to review the outcomes of aortic arch surgery in neonates and infants. Materials and Methods: We retrospectively analyzed patients who underwent aortic arch reconstruction with or without intracardiac anomalies between 2017 and 2022. The subjects were categorized into two groups based on the arch reconstruction technique employed: group 1 underwent patch aortoplasty via sternotomy, whereas group 2 underwent arch reconstruction without a patch via thoracotomy. Demographic information, morbidity rates, and mortality statistics were extracted from the departmental database for the analysis. Results: This study enrolled 37 patients (25 males and 12 females). Twenty-nine patients were assigned to group 1, while eight patients were allocated to group 2. No significant differences were observed in the preoperative variables between the two groups. The overall median age and weight were 11 days (range: 2-270) and 3.1 kg (range: 1.4-5.6), respectively. Nine patients had a weight <2.5 kg. Twenty-eight patients underwent concomitant cardiac procedures. The 30-day mortality rate was 10.8% (n=4), with all deceased patients belonging to STAT Mortality Category 4 (n=31). No mortality was observed in the patients with isolated hypoplastic aortic arch or concomitant ventricular septal defect repair. At a median follow-up of 27 months, three patients in group 2 developed restenosis and underwent surgical correction. In group 1, restenosis was observed in only one patient, who was treated with balloon angioplasty. The incidence of recurrent arch obstruction was significantly higher in group 2 (p=0.02). Conclusion: Aortic arch repair with patch through sternotomy represents a safe and efficacious approach, offering potential for intervention in intracardiac anomalies. The implementation of a patch facilitates tension-free anastomosis and optimal arch geometry, while demonstrating an acceptable rate of restenosis.